Short Nylon Fibers Waste Modified with Glycidyl 3-Pentadecenyl Phenyl Ether to Reinforce Styrene Butadiene Rubber Tread Compounds - Lan Cen; Guo-zheng Lv; Xin-wen Tan; Zhan-lin Gong (Advances in Polymer Technology)
The utilization of waste fibers represents an important environmental benefit and great economic savings for the community. In this study short nylon fibers waste was modified with Glycidyl 3-Pentadecenyl Phenyl Ether (GPPE) in the presence of Triethylamine/Ammonium persulfate by a simple two-step procedure. The reinforcing effects of modified fibers (MNSF-2) on the vulcanization characteristics, mechanical properties, dynamic mechanical properties, and the wear resistant property of Styrene Butadiene Rubber (SBR) tread compounds were investigated. The addition of the MNSF-2 resulted in slightly lower minimum torque (ML) and maximum torque (MH), as well as longer cure time (t90) and scorch time (t10) of tread compounds. The deterioration of tensile strength and elongation at break of the tread compound containing short nylon fibers waste (NSF) was apparent. Conversely, the modified fibers showed reinforcing effect on tread compounds. The tensile strength values of compounds increased with MNSF-2 content, passed through a maximum value, and then reduced slightly. The modulus and the tear strength of compounds increased significantly with fiber loadings. The highest tear strength value was observed in 8phr MNSF-2 reinforced SBR compounds, 31.9% higher than that of the gum compound. Meanwhile elongation at break of MNSF-2 compound maintained a relative high value than that of NSF/SBR compound. The addition of NSF exaggerated wear volume of compounds. However, the wear resistance of MNSF-2 compounds was superior to that of NSF compounds and comparable with that of the gum compound. The DMA results reveal that E′ and tan⁡δ values decreased at elevated temperature. Meanwhile enhanced storage modulus in MNSF-2/SBR tread compound can be observed. It is worth highlighting that MNSF-2/SBR compounds show higher tan⁡δ at 0°C, indicating improved wet traction of tread compounds, while tan⁡δ at 60°C maintains almost the same value as that of the gum sample. The results of this study are encouraging, demonstrating that the use of short nylon fibers waste in composites offers promising potential for the green tire application.